The Impact of the Application of Islamic Values in Natural Science (IPA) Learning on the Learning Motivation of Class VII Students at MTsN 1 Enrekang - Jupri Jupri; Andi Abd Muis; Suredah Hamid; Andi Fitriani Djollong; Amir Patintingan (CV. Gerasi Insan Nusantara, 2026)
This study began with initial observations showing that approximately 58% of students at MTsN 1 Enrekang demonstrated low intrinsic learning motivation in Natural Science (IPA) classes. This condition is a serious concern, considering that science is an essential subject in developing students‘ scientific and logical thinking skills. Therefore, this research aims to explain the implementation of Islamic values in Natural Science learning and to describe the relationship between sincerity in learning (ikhlas), responsibility, and love of knowledge in shaping the learning motivation of seventh grade students at MTsN 1 Enrekang. This research employed a qualitative approach with a descriptive research design, focusing on the process, experiences, and meanings of applying Islamic values in science learning. The data were collected through classroom observations, interviews with science teachers, students, homeroom teachers, and other related parties, as well as documentation studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while the validity of the data was ensured through triangulation techniques. The findings revealed that sincerity in learning was internalized through the cultivation of learning intentions as an act of worship. Responsibility was developed through habituation of discipline and consistency in participating in science learning activities. Meanwhile, love of knowledge was fostered by connecting scientific concepts with the greatness and order of Allah SWT‘s creation. These three values were integrated pedagogically and spiritually, reinforcing one another and contributing to the continuous development and strengthening of students‘ learning motivation, as indicated by increased interest, active participation, seriousness, and responsibility in science learning. This study demonstrates that the implementation of Islamic values in science learning can holistically enhance students‘ learning motivation.